2015
DOI: 10.1038/cddis.2015.313
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression of cancer stem cell marker CD133 by tumor suppressor p53

Abstract: Novel therapeutic strategies are needed to overcome cancer recurrence, metastasis, and resistance to chemo- and radiotherapy. Cancer stem cells (CSCs) are major contributors to the malignant transformation of cells due to their capacity for self-renewal. Although various CSC markers have been identified in several types of tumors, they are primarily used as cancer-prediction markers and for the isolation of CSC populations. CD133, one of the best-characterized CSC markers in distinct solid tumor types, was sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 58 publications
2
68
1
1
Order By: Relevance
“…The present study demonstrated that wild-type p53 transactivated the promoter of the CD133 gene, indicating that the CD133 gene may be a novel target of p53 in colorectal cancer. Although it was previously reported that p53 transcriptionally suppressed CD133 expression (35), p53 may function with different transcription factors in the context of colorectal cancer to maintain the stem cell properties of HCT116 cells, which may be independent of the tumor suppressor role of p53 in other types of cancer. The specificity and robustness of CD133 as a colorectal CSC marker may also need further investigation (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that wild-type p53 transactivated the promoter of the CD133 gene, indicating that the CD133 gene may be a novel target of p53 in colorectal cancer. Although it was previously reported that p53 transcriptionally suppressed CD133 expression (35), p53 may function with different transcription factors in the context of colorectal cancer to maintain the stem cell properties of HCT116 cells, which may be independent of the tumor suppressor role of p53 in other types of cancer. The specificity and robustness of CD133 as a colorectal CSC marker may also need further investigation (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…p53 recruits histone deacetylase 1 (HDAC1) to the CD133 promoter and reduces histone H3 acetylation. Reduction in CD133 expression inhibits tumor cell proliferation, colony formation and the expression of Nanog, Oct4, Sox2 and c-Myc stemness transcription factors [104]. …”
Section: Introductionmentioning
confidence: 99%
“…HDACs operate by direct association with DNA-binding factors and by incorporation into large multifunctional repressor complexes such as Sin3, NuRD, and PRC2 [12]. In addition to functions in chromatin remodeling, HDACs deacetylate certain transcription factors, such as P53 [13], resulting in their decreased activity. HDACs form a large family, of which class I HDACs, including the closely related proteins HDAC1 and HDAC2, show the strongest histone deacetylase activity[14].…”
Section: Introductionmentioning
confidence: 99%